Leishmania Hijacks Myeloid Cells for Immune Escape - Martínez-López, María; Soto, Manuel; Iborra, Salvador; Sancho, David (Frontiers in Microbiology, 2018)
Protozoan parasites of the Leishmania genus are the causative agents of leishmaniasis, a group of neglected tropical diseases whose clinical manifestations vary depending on the infectious Leishmania species but also on host factors. Recognition of the parasite by host myeloid immune cells is key to trigger an effective Leishmania-specific immunity. However, the parasite is able to persist in host myeloid cells by evading, delaying and manipulating host immunity in order to escape host resistance and ensure its transmission. Neutrophils are first in infiltrating infection sites and could act either favoring or protecting against infection, depending on factors such as the genetic background of the host or the parasite species. Macrophages are the main host cells where the parasites grow and divide. However, macrophages are also the main effector population involved in parasite clearance. Parasite elimination by macrophages requires the priming and development of an effector Th1 adaptive immunity driven by specific subtypes of dendritic cells. Herein, we will provide a comprehensive outline of how myeloid cells regulate innate and adaptive immunity against Leishmania, and the mechanisms used by the parasites to promote their evasion and sabotage. Understanding the interactions between Leishmania and the host myeloid cells may lead to the development of new therapeutic approaches and improved vaccination to leishmaniases, an important worldwide health problem in which current therapeutic or preventive approaches are limited.